The Use of Glass from Photovoltaic Panels at the End of Their Life Cycle in Cement Composites - Kateřina Máčalová (MDPI AG, 2021)
This article deals with the use of photovoltaic panels at the end of their life cycle in cement composites. Attention is focused on the properties of cement composite after 100% replacement of natural aggregate with recycled glass from photovoltaic panels. This goal of replacing natural filler sources with recycled glass is based on the updated policy of the Czech Republic concerning secondary raw materials for the period of 2019–2022, which aims to increase the self-sufficiency of the Czech Republic in raw materials by replacing primary sources with secondary raw materials. The policy also promotes the use of secondary raw materials as a tool to reduce the material and energy demands of industrial production and supports the innovations and development of a circular economy within business. The research has shown that it is possible to prepare cement composite based on recycled glass from solar panels, with compressive and flexural strength after 28 days exceeding 40 MPa and 4 MPa. Furthermore, a possible modification of the cement composite with different pigments has been confirmed, without disrupting the contact zone.